1992
DOI: 10.1111/j.1365-2249.1992.tb05824.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-endothelial cell antibodies in nephropathia epidemica and other viral diseases

Abstract: SUMMARYIncreased capillary permeability is a central feature of the severe forms of haemorrhagic fever with renal syndrome (HFRS) and occurs also, though less frequently, in nephropathia epidemica (NE), one of the milder forms of this syndrome, caused by Puumala virus. We therefore searched for antiendothelial cell antibodies (AECA) in patients with NE and in those with other presumed or serologically proven acute viral illnesses. By enzyme immunoassay, using human umbilical vein endothelial cells (HUVEC) as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Specifically, the vascular endothelium is a sensitive target of the inflammatory response in several autoimmune diseases including systemic lupus erythematosus and rheumatoid arthritis (1012). While the endothelium is a dynamic structure involved in tissue homeostasis, luminal inflammation and subsequent dysfunction result in clinically significant end-organ injury.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the vascular endothelium is a sensitive target of the inflammatory response in several autoimmune diseases including systemic lupus erythematosus and rheumatoid arthritis (1012). While the endothelium is a dynamic structure involved in tissue homeostasis, luminal inflammation and subsequent dysfunction result in clinically significant end-organ injury.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies [ 33 ] we found rheumatoid factors, recognized in viral illnesses, circulating immune complexes, and increased levels of IgM in all 18 patients with PUUV-induced disease; the levels of IgG and IgA increased during the clinical disease but remained normal. We also found anti-endothelial cell antibodies in NE and other viral diseases [ 34 ]. We detected autoimmune polyendocrinopathy and hypophysitis after PUUV infection [ 35 ].…”
Section: Role Of Different Factors In the Variationmentioning
confidence: 93%